Geografia, religião e política: a “ressacralização” do Estado pelos pentecostais e neopentecostais no Brasil contemporâneo - Melo, Letycia Lisboa (2023)
The present work aims to identify the main expressions produced by the growing performance of Pentecostal and neo-Pentecostal evangelical groups in the current Brazilian political space, with the support of denominations of these religious segments and their respective leaders, based, therefore, in certain theological, political and ideological fields, which were detected and analyzed by the research. The presence of this class in politics, which was already expressive, multiplied exponentially after the election of the far-right evangelical candidate Jair Bolsonaro to the presidency in 2018, inaugurating in the country the establishment of the so-called "bolsonarist" ideological movement, supported by many Pentecostal and neo-Pentecostal institutions and denominations that won, in turn, popularity, influence and political power. Thus, in recent years, the Pentecostal and Neo-Pentecostal groups have entered, increasingly, directly and indirectly, public life, progressively becoming a decisive class in electoral processes at all scales, generating, as the research points out, many expressions and transformations in the symbolic field and in the lived space of the country through its peculiar action directed, mainly, to the right and extreme right of the political spectrum, aiming at the establishment, in the form of a political spectrum. discourses, bills of Law and Laws, of conservative, moralistic, neoliberal, exclusivist principles and aligned with the interests of Capital, especially, sighted in the proposed projects for education and school spaces of the state of Minas Gerais and the city of Uberlândia-MG, which also became objects of analysis of this work reflecting, in the analyzed regions, a trend experienced at the national level. Key-words: politics; evangelical; pentecostal; neo-pentecostal; “Bolsonarismo”; education.